Referred otalgia: epidemiological profile - Gandhi, Saurabh; Soni, Hiren (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Otalgia (earache) is one of the commonest presenting complaints of the patients visiting ENT OPD and wide varieties of otological diseases are associated with it. Not only that but surrounding structural pathology of head and neck can at times manifest as otalgia (because of complex innervations of ear) known as referred otalgia. Methods: This research was carried out on patients visiting ENT OPD complaining of earache. All patients’ data including age, sex, complaints, affected ear, findings of ear, nose, throat, head and neck were recorded in proforma. Data were analyzed, primary and referred otalgia was recorded. Results: Out of hundred patients with otalgia, 31% had referred otalgia of this 54.8% were men and 45.2% were women. Commonest etiology of reoffered otalgia was tonsillitis followed by dental causes. Significant (12.9%) patient had underlying malignancies. 32.2% had right earache while 45.1% had left earache. Conclusions: A thorough clinical examination of surrounding structures particularly tonsils and teeth should be done as significant number of patient suffered from referred otalgia and while doing this malignancy should be kept in mind as etiology.